The effect of estrus and pregnant sheep serum on in vitro ovine embryo production - Mattimena, J (Indonesian Animal Sciences Society, 2006)
The aim of this research is to observe the influence of estrus sheep serum (ESS) and pregnant sheep serum (PSS) on in vitrous ovine embryo development. The research was carried out in Animal Reproduction Laboratory, Faculty of Animal Husbandry, Padjadjaran university. Oocyte and ovary of local sheep were collected from slaughter house. Maturation, fertilization and embryo culture media were supplemented with 10, 15 and 20% ESS or PSS respectively. Results show that supplementation of 20% ESS had significantly (P<0.05) better maturation rate than those of 10-20% PSS (79.98% vs 58.89-68.97%). However, increasing ESS into 15-20% did not affect the maturation rate (71.86-74.98%). Therefore, 10% estrus sheep serum (ESS) can be used as an alternative serum in the ovine maturation media. The supplementation of ESS or PSS did not significantly increas the fertilization rate and in vitrous ovine embryo development, however, it was suggested to add 10% pregnant sheep serum (PSS) at in vitrous ovine embryo culture. Key Words: Serum, Sheep, Maturation, Fertilization, Embryo